A study to assess the bond strength of acrylic teeth with different retentive features - Savita Dandekeri; Smrithi Mohandas; Sanath K Shetty; Mallikarjuna Ragher; Mohammed Rasheed; Nikhil Raj (Wolters Kluwer Medknow Publications, 2020)
Background and Aim: Flexible denture base has been gaining attention as a denture base material because of its toxicological safety, comfort, and enhanced aesthetics. Debonding of acrylic teeth from the flexible denture base material has posed a great problem to the clinician and patient. This study aimed at comparing the bond strength between flexible denture base with acrylic teeth having different mechanical modifications. Materials and Methods: Forty mandibular molar teeth (Combination Acry Rock, Badia Polesine (Ro), Italy) were used in four groups for mechanical modifications on the ridge lap area. The groups were group 1 (no mechanical modifications), group 2 (round groove 2 mm in diameter and 2 mm deep on the ridge lap surface), group 3 (horizontal slot 2 mm deep, 2 mm wide, and 4 mm long prepared on the ridge lap surface of the teeth), and group 4 (T-shaped groove 2 mm deep, 2 mm wide, and length of 4 mm mesiodistally and 2 mm buccolingually prepared with a straight fissure bur). The acrylic teeth were attached to a wax block of dimension 1.2cm × 1.2cm × 2.5cm. These were flasked and dewaxed, followed by injection molding with Valplast flexible denture base material. The bond strength was assessed by attaching the specimens to universal testing machine tested under a tensile load at a cross-head speed of 1 mm/min till it fractured. Data obtained were statistically evaluated by one-way analysis of variance and post hoc test. Results: There was significant increase in mean bond strength after various mechanical modifications. Group with T-shaped diatoric hole showed greatest bond strength value compared to other groups. Conclusion: Incorporating mechanical retentive features with increased surface area and undercut can improve the bonding of acrylic teeth to flexible denture base.